Bioadhesive hydrogel-coupled and miniaturized ultrasound transducer system for long-term, wearable neuromodulation - Kai Wing Kevin Tang; Jinmo Jeong; Ju-Chun Hsieh; Mengmeng Yao; Hong Ding; Wenliang Wang; Xiangping Liu; Ilya Pyatnitskiy; Weilong He; William D. Moscoso-Barrera; Anakaren Romero Lozano; Brinkley Artman; et al. (Nature Communications)
Abstract Transcranial focused ultrasound is a promising non-invasive method for neuromodulation, particularly for neurodegenerative and psychiatric conditions. However, its use in wearable systems has been limited due to bulky devices and reliance on ultrasound gel, which dehydrates and lacks stable adhesion for long-term use. Here, we present a miniaturized wearable ultrasound device, comparable in size to standard electrophysiological electrodes, integrated with a bioadhesive hydrogel for stable, long-term somatosensory cortical stimulation. Our air-cavity Fresnel lens based self-focusing acoustic transducer was fabricated via a lithography-free microfabrication process, achieving 30.7 W/cm² (1.92 MPa) acoustic intensity and 10 mm focal depth. The hydrogel couplant exhibited less than 13% acoustic attenuation and maintained a stable adhesion force of 0.961 N/cm for 35 days. Using this system, we successfully suppressed somatosensory evoked potentials elicited by functional electrical stimulation over 28 days, demonstrating the device’s potential for long-term, wearable neuromodulation applications.